Physicochemical Characterization and In Vivo Evaluation of Amorphous and Partially Crystalline Calcium Phosphate Coatings Fabricated on Ti-6Al-4V Implants by the Plasma Spray Method - Estevam A. Bonfante; Lukasz Witek; Nick Tovar; Marcelo Suzuki; Charles Marin; Rodrigo Granato; Paulo G. Coelho (International Journal of Biomaterials)
Objective. To characterize the topographic and chemical properties of 2 bioceramic coated plateau root form implant surfaces and evaluate their histomorphometric differences at 6 and 12 weeks in vivo. Methods. Plasma sprayed hydroxyapatite (PSHA) and amorphous calcium phosphate (ACP) surfaces were characterized by scanning electron microscopy (SEM), interferometry (IFM), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FT-IR). Implants were placed in the radius epiphysis, and the right limb of dogs provided implants that remained for 6 weeks, and the left limb provided implants that remained 12 weeks in vivo. Thin sections were prepared for bone-to-implant contact (BIC) and bone-area-fraction occupancy (BAFO) measurements (evaluated by Friedman analysis 𝑃<0.05). Results. Significantly, higher Sa (𝑃<0.03) and Sq (𝑃<0.02) were observed for ACP relative to PSHA. Chemical analysis revealed significantly higher HA, calcium phosphate, and calcium pyrophosphate for the PSHA surface. BIC and BAFO measurements showed no differences between surfaces. Lamellar bone formation in close contact with implant surfaces and within the healing chambers was observed for both groups. Conclusion. Given topographical and chemical differences between PSHA and ACP surfaces, bone morphology and histomorphometric evaluated parameters showed that both surfaces were osseoconductive in plateau root form implants.